Produktivitas Kerja Awak Kapal pada Kapal Tanker Nasional di Indonesia - Kasno, Kasno; Setyawati, Aswanti; Sonny, Imam; Abidin, Zaenal; Anggara, Dian Christopher (Institut Transportasi dan Logistik Trisakti, 2024)
The main problem of the national tanker company, Pertamina Trans Kontinental, is the low productivity of the ship’s crew. The purpose of the study is to find out the performance of the crew commitment, crew motivation and work facilities to improve the company’s work productivity. The data were obtained by interviewing five experts. Questionnaires were distributed to ten people of five experts and five employees of Pertamina Trans Continental. The data, then, were analyzed using AHP (Analytic Hierarchy Process). The results of the study show that some employees still need special guidance and supervision to increase their motivation and commitment and the ship facilities should also be increased. The results of the analysis using AHP show that the highest priority can be seen in work motivation factor and then followed by work commitment and work facilities.